Study of Acute Transfusion Reactions in a tertiary care hospital - Dr. Yashodhara Rajesh Gotekar; Dr. Amruta Khade (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Blood transfusion is an effective way of correcting the hematological needs of patients, but adverse effects do occur during or after transfusion. These adverse events associated with the transfusion of whole blood or one of its components are known as transfusion reactions. Aim: To study the frequency and type of Acute Transfusion Reactions (ATRs) occurred in patients receiving blood transfusions. Materials and Methods: This retrospective observational study was done to know acute transfusion reactions reported to Bharati Vidyapeeth (Deemed to be University) Medical College and Hospital, Blood Bank, Sangli over a period of 5 years (January 2015-December 2019).All ATRs related to whole blood and blood components were analyzed and classified on the basis of their clinical features and laboratory tests. Results: ATRs during or after blood transfusion reported during the five year period were 77 (0.21 %) out of 35,593 units of blood /blood components transfused. ATRs reported were febrile non hemolytic transfusion reactions (FNHTR) 46 (59.74%), allergic Reactions 29 (37.66 %), anaphylactic reactions 2 (2.59 %) in order of frequency. Conclusion: The majority of ATRs were FNHTRs followed by allergic reactions.